Separating intrinsic and scattering attenuation in full waveform sonic logging with radiative transfer theory. Issue 2 (17th January 2018) - Durán, Evert L; van Wijk, Kasper; Adam, Ludmila; Wallis, Irene C
Summary: Fitting the intensity of ensembles of sonic log waveforms with a radiative transfer model allows us to separate scattering from intrinsic attenuation in two wells of the Ngatamariki geothermal field, New Zealand. Independent estimates of scattering and intrinsic attenuation add to the geologic interpretation based on other well log data. Particularly, our estimates of the intrinsic attenuation confirm or refine inferences on fluid mobility in the subsurface. Zones of strong intrinsic attenuation in Well 1 correlate with identified feed zones in three of the six cases, and hint at permeability just above two of the other three zones. In Well 2, intrinsic attenuation estimates help identify all three identified permeable intervals, including a washout.